Relations with the Controllership and the Management of Economic- Financial Information in the New Economy - Menezes, Luiz Leite de; Riccio, Edson Luiz (Review of Business Management, 2007)
This paper analysis the relationships between the Control function and the management of the information used for financial control of the firm. The analysis were based in the fundamental concepts by which information is an instrument that supports management in the control and continuity of operations, and that managers are the main users of that information. In the process of evaluating a firm’s performance the Control function measures the contribution of each area and, as consequence, the manager associated with each one. In this case, the company’s Controller assumes the role of information process manager. The methodology included a literature research in Management, Information Technology and Digital Economy, followed by a field research conducted by questionnaires and interviews with controllers and functional managers. Results showed the emergence of a new model in which the firm’s missions can be planned, measured and obtained in a collaborative way. This is achieved by an effective flow of information, based on intensive utilization of IT by the processes. Highly automated transaction processes and the power of internet change the manner of operating the firms. Professionals are faced with the new variables in the state-of-the-art of measurement models and information for decision making in regard to the future and risks to be taken by the firms. Key-words: Controllership. Information management. Controller. Information technology.